2012
DOI: 10.1088/0004-637x/755/2/87
|View full text |Cite
|
Sign up to set email alerts
|

TWO-DIMENSIONAL MAPPING OF YOUNG STARS IN THE INNER 180 pc OF NGC 1068: CORRELATION WITH MOLECULAR GAS RING AND STELLAR KINEMATICS

Abstract: We report the first two-dimensional mapping of the stellar population and non-stellar continua within the inner 180 pc (radius) of NGC 1068 at a spatial resolution of 8 pc, using integral field spectroscopy in the near-infrared. We have applied the technique of spectral synthesis to data obtained with the instrument NIFS and the adaptive optics module ALTAIR at the Gemini North Telescope. Two episodes of recent star formation are found to dominate the stellar population contribution: the first occurred 300 Myr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
69
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 46 publications
20
69
0
Order By: Relevance
“…Paα line emission can be interpreted as a tracer of young (<30 Myr) star formation or gas emission. Storchi-Bergmann et al (2012) found an episode of young (30 Myr) stellar population in a ring-like structure at ∼100 pc from the nucleus, coincident with the ring of molecular gas detected in the 2.12 µm warm molecular hydrogen line and in cold molecular gas detected by ALMA (García-Burillo et al 2014). We found that the morphology of this young stellar population and cold molecular gas resembles neither the Paα line emission nor the MIR features in the northern ionization cone.…”
Section: The Northern Ionization Conementioning
confidence: 77%
“…Paα line emission can be interpreted as a tracer of young (<30 Myr) star formation or gas emission. Storchi-Bergmann et al (2012) found an episode of young (30 Myr) stellar population in a ring-like structure at ∼100 pc from the nucleus, coincident with the ring of molecular gas detected in the 2.12 µm warm molecular hydrogen line and in cold molecular gas detected by ALMA (García-Burillo et al 2014). We found that the morphology of this young stellar population and cold molecular gas resembles neither the Paα line emission nor the MIR features in the northern ionization cone.…”
Section: The Northern Ionization Conementioning
confidence: 77%
“…Regions of low stellar velocity dispersion have been observed in the inner ≈ 200 pc of nearby Seyferts (Emsellem 2008;Comerón et al 2008) and young to intermediate (10 6 -10 8 yrs old) stellar population have been observed associated to these regions (Riffel et al 2010Storchi-Bergmann et al 2012;Hicks et al 2013). These low velocity dispersion regions have been interpreted as due to a stellar component in the vicinity of the nucleus of Seyfert galaxies that is dynamically colder in comparison to the stars that dominate the detected stellar light in quiescent galaxies (Hicks et al 2013).…”
Section: Estimating the Mass Inflow Ratementioning
confidence: 96%
“…The rotational model we obtained for the stellar velocity field in Sec. 4.1 is not an adequate description of the gaseous velocity field, as the stellar component usually rotates more slowly than the gas (van der Kruit & Freeman 1986;Bottema et al 1987;Noordermeer et al 2008). To acccount for this difference, we fitted the model described in Sect.…”
Section: The Narrower Componentmentioning
confidence: 99%
“…This torus/reservoir, with size ranging from a few to several tens of parsecs, has been studied in detail only in nearby AGNs. High spatial resolution observations reveal that molecular gas and dust is largely present (e.g., Muller-Sanchez et al 2009;Krips et al 2011;Diamond-Stanic & Rieke 2012;Sani et al 2012;Hönig et al 2013), often accompanied by star formation (e.g., Davies et al 2007;Storchi-Bergmann et al 2012). The dust distribution looks quite complex, with the hot dust located in compact structures, while the warm one is more diffuse (see Hönig et al 2013).…”
Section: The Reservoirmentioning
confidence: 99%